Presenteeism as a consequence of workplace bullying: Mediating role of emotional exhaustion and moderation of climate for conflict management - Khalida Naseem; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This study probes the link between workplace bullying, emotional exhaustion and presenteeism in employees of public and private sector service organizations. Based on affective events theory, this study found that emotional exhaustion mediates the relationship between bullying and employee presenteeism. However, the climate for conflict management (CCM) was found to moderate the aforementioned relationship. Data taken from 2250 employees working in health, education and forest departments support the assumptions that workplace bullying and presenteeism are partially mediatedby individual's perceived emotional exhaustion and that the CCM moderates this mediated association. This mediated moderation model suggests that workplace bullying emotionally exhausts employees, who despite being present at workplace cannot perform to their full potential. On the other hand, organizations that are active in conflict management practices may be able to prevent and reduce the adverse effects of workplace bullying
Keywords: 330; workplace bullying; emotional exhaustion; climate for conflict management; presenteeism; conflict management practices